Role of Angiotensin Type 2 Receptor on Nitric Oxide Production Response to Angiotensin II Administration in Ovariectomised Rats Treated with Estradiol - Tahereh Safari; Mehdi Nematbakhsh (International Journal of Preventive Medicine, 2014)
Background: Renin-angiotensin system activity is gender related. The vasodilatory response of angiotensin II (AngII) angiotensin type 2 receptor (AT2R) may involve nitric oxide (NO) production. We attempted to find the role of AT2R on NO formation response to AngII administration in ovariectomised rats treated with estradiol (OVE). Methods: A total of 33 female Wistar rats were divided into 3 groups; intact animals, ovariectomised treated with placebo (OVX) and OVE. At 2 weeks later, all animals were subjected to anesthetize and catheterize and each group was divided into two subgroups that received AT2R antagonist (PD123319) or vehicle. Each animal was subjected to 1 h continuous infusion of AngII (~20 μg/kg/h) and the level of NO metabolite (nitrite) was measured before and after AngII infusion. Results: At the presence of AT2R, the serum level of nitrite in response to AngII administration in OVE groups increased significantly (P < 0.05). Conclusions: However, this increase was abolished by AT2R antagonist. It seems that AT2R involves nitrite production response to AngII in OVE.